Impacts of monoculture cropland to alley cropping agroforestry conversion on soil N2O emissions. Issue 1 (3rd November 2022) - Shao, Guodong; Martinson, Guntars O.; Corre, Marife D.; Luo, Jie; Niu, Dan; Bischel, Xenia; Veldkamp, Edzo
Abstract: Monoculture croplands are a major source of global anthropogenic emissions of nitrous oxide (N2 O), a potent greenhouse gas that contributes to ozone depletion. Agroforestry has the potential to reduce N2 O emissions. Presently, there is no systematic comparison of soil N2 O emissions between cropland agroforestry and monoculture systems in Central Europe. We investigated the effects of converting the monoculture cropland system into the alley cropping agroforestry system on soil N2 O fluxes at three sites (each site has paired agroforestry and monoculture) in Germany, where agroforestry combined crop rows and poplar short‐rotation coppice (SRC). We measured soil N2 O fluxes monthly over 2 years (March 2018–January 2020) using static vented chambers. Annual soil N2 O emissions from agroforestry ranged from 0.21 to 2.73 kg N ha −1  year −1, whereas monoculture N2 O emissions ranged from 0.34 to 3.00 kg N ha −1  year −1 . During the rotation of corn crop, with high fertilization rates, agroforestry reduced soil N2 O emissions by 9% to 56% compared to monocultures. This was mainly caused by low soil N2 O emissions from the unfertilized agroforestry tree rows. Soil N2 O fluxes were predominantly controlled by soil mineral N in both agroforestry and monoculture systems. Our findings suggest that optimized fertilizer input will further enhance the potential of agroforestry for mitigating N2 O emissions. Abstract : Agroforestry is an agricultural management practice that has been widely promoted for its potential to reduce N2 O emissions and to help improve energy security. We investigated the effects of converting cropland monoculture to alley cropping agroforestry systems on soil N2 O fluxes at three sites in Germany, where the agroforestry systems combined crop rows and hybrid poplar short rotation coppice. Soil N2 O fluxes were predominantly controlled by mineral N, and substantially affected by crop choice and timing and magnitude of fertilizer application in both agroforestry and monoculture systems. Our findings suggest that optimized fertilizer input will further enhance the potential of agroforestry for mitigating N2 O emissions.